Guanidine-Catalyzed γ-Selective Morita–Baylis–Hillman Reactions on α,γ-Dialkyl-Allenoates: Access to Densely Substituted Heterocycles - Selig, Philipp; Turočkin, Aleksej; Raven, William (Synlett, 2013)
N-Methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD) was discovered as an excellent catalyst for the Morita–Baylis–Hillman reaction for previously hard-to-activate α,γ-dialkyl allenoate substrates. The obtained densely substituted allenic alcohols, which are generally inaccessible with other Lewis base catalysts, could be further converted into 2,5-dihydrofuran and 2H-pyran-2-one heterocyclic structures with challenging substitution patterns.
Keywords: allenes; catalysis; nucleophiles; guanidines; cyclization